Comtemporary educational research in Slovakia - Štefan Švec (Czech Pedagogical Society, 2010)
In the paper, the author presents his views on the definition of the termsresearch and educational science. He also briefly summarises the institutional basis ofeducational research and development in Slovakia and discusses the current state ofeducational science and its supportive activities, including doctoral study programs. Towardsthe end of the article, selected threats within educational science are referred aswell as important objectives for research and development, and evaluation in educationalsciences.